STRATEGI MARKETING PUBLIC RELATIONS ASHRAM GANDHI PURI SEVAGRAM DALAM MEMPERTAHANKAN CITRA POSITIF ORGANISASI - I Wayan Sari Dika; I Gede Sutarya; I Ketut Wardana Yasa (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2021)
The Gandhi Puri Sevagram Ashram, as an organization engaged in the spiritual and educational fields, was reported negatively, causing its image to deteriorate. This makes people familiar with the Gandhi Puri Sevagram Ashram from the negative side, but when the news was slowly stopped by the Marketing Public Relations of the Gandhi Puri Sevagram Ashram by always providing information about activities at the ashram to the public through newspapers and social media. This research focuses on the discussion of (1) Public perceptions of the Gandhi Puri Sevagram Ashram (2) Marketing public relations strategy of Gandhi Puri Sevagram Ashram in maintaining a positive image of the organization (3) Implications of public relations marketing strategy for the image building of Gandhi Puri Sevagram Ashram. The theory used in analyzing are: Consumer Behavior Theory, and Integrated Marketing Communication Theory. This research uses observation methods, in-depth interviews, questionnaires, document studies, and documentation studies. This research finds first, people's perceptions about the Gandhi Puri Sevagram Ashram based on the results of questionnaire data taken from 100 respondents via google form using several predetermined indicators, obtained the average respondent's answer data reached 4.15 so it is classified as good criteria. Secondly, Ashram Gandhi Puri Sevagram's marketing strategy of public relations in maintaining a positive image of the organization has been carried out using a combination of marketing communications through advertising, events and community networks. Third, the implications of the marketing public relations strategy for building the image of the Gandhi Puri Sevagram Ashram can make the ashram better known, the ashram gets the opportunity to serve the community in various fields and the ashram gets a lot of scholarships and groceries from donors.